Cortisol-Induced Increases of Plasma Oxytocin Levels Predict Decreased Immediate Free Recall of Unpleasant Words - Tops, Mattie; Buisman-Pijlman, Femke; Boksem, Maarten A.; Wijers, Albertus A.; Korf, Jakob (Frontiers in Psychiatry, 2012)
Cortisol and oxytocin have been shown to interact in both the regulation of stress responses and in memory function. In the present study we administered cortisol to 35 healthy female subjects in a within-subject double-blind placebo-controlled design, while measuring oxytocin levels, adrenocorticotropic hormone (ACTH) levels, and free recall of pleasant and of unpleasant words. We found that cortisol administration induced both a decrease in oxytocin associated with ACTH suppression and an increase in oxytocin that was independent from ACTH suppression. This cortisol-induced increase in plasma oxytocin was associated with a selective decrease in immediate free recall of unpleasant words from primacy positions. The present results add to evidence that cortisol-induced increases in oxytocin could mediate some of the effects of stress and cortisol treatment on memory, and possibly play a role in the regulation of the hypothalamo-pituitary-adrenal stress response. This mechanism could significantly impact affective and social behaviors, in particular during times of stress.